S121 Assessment of interlobarcollateral ventilation prior to endobronchial valves treatment for severe emphysema. (14th November 2013) - Banerjee, Sk; Babar, J; Balan, A; Mahadeva, R
Abstract : Bronchoscopic lung volume reduction (BVLR) with one-way endobronchial valves are employed to reduce hyperinflation to improve symptoms and lung function. The clinical benefits of Zephyr (PulmonX) valves in achieving target lobe volume reduction are most marked in those without collateral ventilation (CV) between ipsilateral non-target and target lobes. The presence of CV can be assessed by visual assessment of fissure integrity on CT scan and by measurement of flow and resistance following balloon catheter occlusion of the target lobe bronchus (Chartis; PulmonX). We have compared these two techniques for assessing collateral ventilation in patients with severe emphysema referred for EBV treatment. Two respiratory radiologists reviewed the CT images in 19 consecutive patients. Fissure integrity was classified as complete, incomplete minor defect, incomplete major defect. Chartis assessment for CV status was performed on potential target lobes in the same patients, and results compared for the two methods. There was 57.9% (11/19), 63.2% (12/19) and 78.9% (15/19) agreement between radiologists on fissure analysis of the right horizontal (RH), right oblique (RO) and left oblique (LO) fissures (Table 1). In 11 patients with no collateral ventilation on Chartis evaluation to the target lobe; Radiologist 1 reported 9 complete and 2 with incomplete minor defects compared to Radiologist 2; 10 complete and one with incomplete major defect. In 8 found to be CV positive by Chartis, radiologist 1; 3 complete, 3 incomplete major and 2 incomplete minor defects, and radiologist 2; 4 complete, 2 incomplete major and 2 incomplete minor defects. In conclusion, there was inter-observer difference in reporting fissure integrity particularly for right sided fissures, with better agreement for left oblique fissure. However, when experienced chest radiologists scored fissures as complete, there was a high correlation with CV negative status by Chartis. If radiologists scored fissures as incomplete major only one case was found to be CV negative whilst 2 CV negative cases were incomplete minor. This data indicates that visual assessment of fissure integrity by experienced respiratory radiologists can be used as a screening tool to determine appropriateness for subsequent Chartis EBV assessment.